Effects of an individualized soccer match simulation on vertical stiffness and impedance - Cone, J. R.; Berry, N. T.; Goldfarb, A. H.; Henson, R. A.; Schmitz, R. J.; Wideman, L.; Shultz, S. J. (The Journal of Strength and Conditioning Research, 2012)
An observed relationship between soccer match duration and injury has led to research examining the changes in lower extremity mechanics and performance with fatiguing exercise. Because many fatigue protocols are designed to result in substantial muscular deficits, they may not reflect the fatigue associated with sport-specific demands that have been associated with the increasing incidence of injury as the match progresses. Thus, the aim of this study was to systematically analyze the progressive changes in lower extremity mechanics and performance during an individualized exercise protocol designed to simulate a 90-minute soccer match. Previous match analysis data were used to systematically develop a simulated soccer match exercise protocol that was individualized to the participant's fitness level. Twenty-four National Collegiate Athletic Association Division I soccer players (12 men, 12 women) participated in 2 testing sessions. In the first session, the participants completed the Yo-Yo Intermittent Recovery Test Level 1 to assess their fitness level and determine the 5 submaximal running intensities for their soccer match simulation. In the second test session, progressive changes in the rating of perceived exertion (RPE), lower extremity performance (vertical jump height, sprint speed, and cutting speed), and movement mechanics (jumping vertical stiffness and terminal landing impedance) were measured during the soccer match simulation. The average match simulation running distance was 10,165 ± 1,001 m, consistent with soccer match analysis research. Time-related increases in RPE, and decrements in sprinting, and cutting speed were observed, suggesting that fatigue increased as the simulation progressed. However, there were no time-related decreases in vertical jump height, changes in lower extremity vertical stiffness in jumping, or vertical impedance during landing. Secondary analyses indicated that the coordinative changes responsible for the maintenance of stiffness and impedance differed between the dominant and nondominant limbs. Despite an increase in RPE to near exhaustive levels, and decrements in sprint and cutting performance, the participants were able to maintain jump performance and movement mechanics. Interestingly, the coordinative changes that allowed for the maintenance of vertical stiffness and impedance varied between limbs. Thus, suggesting that unilateral training for performance and injury prevention in soccer-specific populations should be considered.